2017
DOI: 10.1016/j.chemosphere.2017.03.025
|View full text |Cite
|
Sign up to set email alerts
|

Sea salt sodium record from Talos Dome (East Antarctica) as a potential proxy of the Antarctic past sea ice extent

Abstract: Antarctic sea ice has shown an increasing trend in recent decades, but with strong regional differences from one sector to another of the Southern Ocean. The Ross Sea and the Indian sectors have seen an increase in sea ice during the satellite era (1979 onwards). Here we present a record of ssNa flux in the Talos Dome region during a 25-year period spanning from 1979 to 2003, showing that this marker could be used as a potential proxy for reconstructing the sea ice extent in the Ross Sea and Western Pacific Oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 58 publications
0
17
0
Order By: Relevance
“…Concentrations of Na + from an array of West Antarctic ice cores revealed at positive correlation with winter SIE at some sites but not others [48]. In East Antarctica (Talos Dome), Severi et al (2017) [28] found a good correlation between September SIE maxima and sodium flux and the same relationship is observed at Dome Fuji [49]. In both these cases, the correlations were stronger when converting sodium concentrations to fluxes, which take into account of the amount of snowfall each year.…”
Section: Sea Saltsmentioning
confidence: 87%
See 1 more Smart Citation
“…Concentrations of Na + from an array of West Antarctic ice cores revealed at positive correlation with winter SIE at some sites but not others [48]. In East Antarctica (Talos Dome), Severi et al (2017) [28] found a good correlation between September SIE maxima and sodium flux and the same relationship is observed at Dome Fuji [49]. In both these cases, the correlations were stronger when converting sodium concentrations to fluxes, which take into account of the amount of snowfall each year.…”
Section: Sea Saltsmentioning
confidence: 87%
“…The highest resolution marine record is the multi-decadal record from Joides basin, western Ross Sea [52]. The resolution of between 9 and 23 years could be compared with ice core records, such as Whitehall Glacier in northern Victoria Land [30] and Talos Dome [28]. Both ice core sites capture changes in the Ross Sea during the 20th century.…”
Section: Temporal Coveragementioning
confidence: 99%
“…Rankin et al, 2002;2004). Moreover, this finding raises the possibility of using sea salt or sodium recorded in ice cores as a potential sea-ice extent proxy for past climates (Wolff et al, 2003;Abram et al 2013;Severi et al, 2017).…”
Section: Introductionmentioning
confidence: 84%
“…It has been found that suspended blowing-snow particles follow a two-parameter gamma distribution function f (d i , α, β), with the α shape parameter and β scale parameter following a simple relationship of αβ = D, where D is mean diameter in microns of blown-snow particles (e.g. Schmidt, 1982;Dover, 1993).…”
Section: Blowing-snow Size Distributionmentioning
confidence: 99%